Participatory blended learning model to enhance school and parent partnerships in elementary schools - Hardianto, Deni; Haryanto, Haryanto (Association for Scientific Computing Electrical and Engineering(ASCEE), 2025)
This study aims to examine the effectiveness of a participatory blended learning model in enhancing knowledge and strengthening partnerships between schools and parents. A quasi-experimental pre-test–post-test group design was employed, involving 60 respondents selected as participants in the intervention. The model was designed to integrate online and face-to-face activities that promote collaborative learning and active parental engagement. The findings reveal that the participatory blended learning model significantly improved parental knowledge and partnership quality, as evidenced by statistically significant gains across five key dimensions: school-parent collaboration, digital-era parenting, positive parenting, healthy family routines, and parental involvement in school programs (p 0.05 for all dimensions). Additionally, improvements were observed in participation in parenting classes, inspiration class initiatives, family habit development, and involvement in school committees or associations. This study contributes to the field by demonstrating how participatory blended learning can serve as an effective strategy to bridge communication and cooperation gaps between schools and families, ultimately fostering a more inclusive and supportive educational environment.